The Importance of Building a Business by Utilizing the Web for Millennials (Case Study on “Trendcafe” Fashion) - Yoeyong Rahsel; Andino Maseleno (Siber Nusantara of Economic and Finance Review, 2025)
This study will further discuss the importance of building a business by utilizing the web for the millennial generation, as well as the technical skills and understanding of how to build and manage websites, search engine optimization (SEO), and marketing through social media. Thus, through this web-based business, there will be various advantages and it can provide useful insights for utilizing technology for business success in the future.